Mendorong Pelaku Usaha Bogor Menentukan Harga Pokok Produksi - Nugroho, Herbirowo; Ichsan, Taufikul; Sixpria, Nedsal; Ramadhani, Annisa Alifa (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
One of the difficulties experienced by SMEs, especially in the Bogor Regency area, is how to determine the right selling price. The situation faced by SMEs is that if they sell products at high prices, the products will not sell in the market because of intense competition. If you sell products at low prices, SMEs will experience business losses. Therefore, adequate understanding is needed, especially in terms of planning production costs which will form the cost of product. The aim of this community service activity is to provide skills training in calculating the correct cost of production as a basis for determining optimal selling prices for SMEs in the Bogor Regency area who have so far only relied on cost estimates without considering the cost object. Keywords,,SME’s, cost of product